Dysbiosis of Oral Microbiota During Oral Squamous Cell Carcinoma Development - Sarkar, Purandar; Malik, Samaresh; Laha, Sayantan; Das, Shantanab; Bunk, Soumya; Ray, Jay Gopal; Chatterjee, Raghunath; Saha, Abhik (Frontiers in Oncology, 2021)
Infection with specific pathogens and alterations in tissue commensal microbial composition are intricately associated with the development of many human cancers. Likewise, dysbiosis of oral microbiome was also shown to play critical role in the initiation as well as progression of oral cancer. However, there are no reports portraying changes in oral microbial community in the patients of Indian subcontinent, which has the highest incidence of oral cancer per year, globally. To establish the association of bacterial dysbiosis and oral squamous cell carcinoma (OSCC) among the Indian population, malignant lesions and anatomically matched adjacent normal tissues were obtained from fifty well-differentiated OSCC patients and analyzed using 16S rRNA V3-V4 amplicon based sequencing on the MiSeq platform. Interestingly, in contrast to the previous studies, a significantly lower bacterial diversity was observed in the malignant samples as compared to the normal counterpart. Overall our study identified Prevotella, Corynebacterium, Pseudomonas, Deinococcus and Noviherbaspirillum as significantly enriched genera, whereas genera including Actinomyces, Sutterella, Stenotrophomonas, Anoxybacillus, and Serratia were notably decreased in the OSCC lesions. Moreover, we demonstrated HPV-16 but not HPV-18 was significantly associated with the OSCC development. In future, with additional validation, this panel could directly be applied into clinical diagnostic and prognostic workflows for OSCC in Indian scenario.